31. ANALYSIS OF SOCIAL RELATIONS (IN THE EXAMPLE OF THE INTERPRETATION OF THOMAS AQUINAS) - Salimov Bakhriddin Lutfullaevich. Mullaeva Komila Kamolovna (Innovative technologies in construction Scientific Journal, 2023)
Abstract The article shows that the views of Thomas Aquinas and his philosophical position are very different from those of Aurelius Augustine, and this difference is first of all evident in the attitude towards religion, and it is emphasized that Thomas Aquinas repeatedly taught that religion is of decisive importance in the life of a person, society and the existence of the state within the framework of social relations.